Peramalan Permintaan Daging Sapi Nasional Menggunakan Metode Multifactors High Order Fuzzy Time Series Model - Taufan Nugraha; Muhammad Tanzil Furqon; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Beef is a commodity whose demand level is always high because it is a livestock product that has nutritional value to obtain protein requirement for society. Increase in beef demand in Indonesia has not been matched by beef production, in terms of both quality and quantity. Beef demand is influenced by beef production, beef consumption, and income levels. In anticipation of the increasing demand for beef, it is necessary to forecast to estimate future demand for beef. To make the forecasting there are various methods used, one of them is the method of multifactors high order fuzzy time series model. The method is a method of forecasting that uses antecedent factor and more than one order, which is considered better than using only one antecedent factor (Lin & Yang, 2009). This research obtained the average forecasting error rate (AFER) of 6.648381805287571% which shows that the smaller error value means the level of accuracy.